2020
DOI: 10.3390/nu12092548
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cow-Milk Protein Supplementation in Elderly Population: Systematic Review and Narrative Synthesis

Abstract: Background. To review currently available evidence on the effect of cow-milk proteins supplementation (CPS) on health in the elderly. Methods. Five electronic databases (Pubmed, Web of Science, Embase, Cochrane Library, ClinicalTrials.gov) were searched for studies about CPS among older people. All types of publications were included, with the exception of systematic reviews, meta-analyses, opinion letters, editorials, case reports, conference abstracts and comments. An additional search in Google Scholar and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 149 publications
0
7
0
Order By: Relevance
“…These subjects received 20 g/day of whey protein, obtained a positive effect on muscle mass, reduced required assistance, and increased general well-being in the active group compared to the placebo group. [12] Interestingly, whey protein was already used in COPD patients, and in that study, the author performed a single-blinded placebocontrolled trial with 40 COPD patients. They found after 8 weeks an increase of fat-free mass, body protein, handgrip strength, and quality of life, and in the opposite, a decrease in interleukin-6 levels, a pro-inflammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…These subjects received 20 g/day of whey protein, obtained a positive effect on muscle mass, reduced required assistance, and increased general well-being in the active group compared to the placebo group. [12] Interestingly, whey protein was already used in COPD patients, and in that study, the author performed a single-blinded placebocontrolled trial with 40 COPD patients. They found after 8 weeks an increase of fat-free mass, body protein, handgrip strength, and quality of life, and in the opposite, a decrease in interleukin-6 levels, a pro-inflammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Three systematic reviews demonstrated the effect of β-hydroxy-β-methylbutyrate (HMB) on muscle mass and strength [46][47][48]. Scholars also reported the effects of cow-milk protein supplementation on muscle mass [49] and the effect of whey protein on physical performance [50]. In addition, three systematic reviews demonstrated the effectiveness of nutritional interventions [51][52][53].…”
Section: The Analysis Of Retrieved Articles 321 Sarcopenia and Nutritionmentioning
confidence: 99%
“…Previous systemic review and meta-analysis studies have compared the effects of different protein sources during exercise training [44,[62][63][64][65][66][67], among which the compared protein supplements included whey [44,[62][63][64][65]67], milk [44,63,65,67], casein [44,62,65,67], beef [63,64], soy [62,63,65,67], and cereal protein [63,65]. However, all such protein supplements were not yet fully compared in single meta-analysis study and the most effective treatment option remains unknown.…”
Section: Introductionmentioning
confidence: 99%